English Sentence Writing for Kids at SDN 1 Unggulan Pulau Morotai - Sutrisno, Dwi Budidarma; Martora, Jasmal; Basri, Megawati (Universitas Pendidikan Nasional, 2024)
English class consists of four main skills including listening, reading, speaking and writing. However, most of the time, writing has almost always received the least attention. This activity aims to introduce the English sentence writing highlighting subject-predicate-object-complement to 25 of fifth grader elementary school students throughout once a week meeting for one month in November at SDN Unggulan 1 Pulau Morotai. The methodology for this activity includes a lecture, a game using four different colors of cards with words in English and Indonesia, a game with one color of cards with words in English and Indonesia, and then a written exam quiz. The result shows that (1) Students are excited and motivated learning English writing through games (2) Students are not only excel in four different colors cards game but also in one color cards game (3) The result from quiz at the last meeting shows more than half of the students (14 out of 25 students) can answers half of the questions right, while approximately one-third of the students (8 out of 25 students) earn excellent scores. In other words, the program that had been done is impactful for students that can be seen by their understanding of English sentence writing using subject-predicate-object-complement and ability to form a correct sentence.